Building Information Modeling (BIM) for Dams-Literature Review and Future Needs - Yunitta Chandra Sari; Catur Ayu Wahyuningrum; Nindyo Cahyo Kresnanto (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
Dam is a structure with high beneficial values and these include, serving as the source of raw water supply and electrical energy, ensuring flood reduction, tourist attractions, and habitat protection. It is, however, associated with a very complex development process ranging from the planning/design, construction, as well as operation and maintenance. Therefore, there is a need for special attention, accuracy, and good coordination at every stage from the parties involved as well as the integration of all fields starting from the Architecture, Engineering, and Construction (AEC) elements. Moreover, ensuring an effective and efficient construction process presents a serious challenge for the owner/government, designers, consultants and contractors which is now being resolved through the use of a technological innovation known as the Building Information Modeling (BIM).This study was conducted to determine the scientific developments of BIM for dam management and also to identify further related areas to be researched in the future. Moreover, the analysis was concentrated on the potential added value of the technological innovations on dams, explained its advantages, and assesses the potential challenges hampering its effectiveness in Indonesia. It was discovered that the use of BIM for dam projects is possible as long as there are adequate government regulations and the availability of qualified human resources while the consequence would be an increase in the investment cost. The findings of this research are expected to encourage the use of BIM in dam construction and management in Indonesia and also to increase efficiency and effectiveness in all aspects.